3(5x-4)=8x+2
- print Print
- list Cite
Expert Answers
calendarEducator since 2012
write937 answers
starTop subjects are Science, Math, and Social Sciences
We can say that this problem is looking for the value of x.
3(5x - 4) = 8x + 2
The first thing to do is to simplify the equation by removing the parenthesis. We can do that if we multiply 3 with (5x - 4);
15x - 12 = 8x + 2
Next, we should combine like terms.
----->add 12 on both sides
15x - 12 + 12 = 8x + 2 + 12
15x = 8x + 14
----->subtract 8x on both sides
15x - 8x = 8x - 8x + 14
7x = 14
To solve for x, we divide both sides by 7.
7x = 14
--- ---
7 7
therefore the answer is x = 2.
Related Questions
- Evaluate the limit of function (7x^2+5x)/(8x^3+6x), x-->infinity.
- 1 Educator Answer
- Find all the roots of f(x) = x^4-2x^3+5x^2-8x+4
- 1 Educator Answer
- Factorise 2x^2 - 5x + 3
- 1 Educator Answer
- Factor the expression by removing the common factor with the smaller exponent. 8x3(5x –...
- 1 Educator Answer
- Find limits: 1.) lim x-->2 (8-x^3)/(x^2-5x+6) 2.) lim x-->-1 (x^2-5x+6)/(x^2-3x+2) 3.) lim...
- 2 Educator Answers
3(5x-4)=8x+2
7x=14
x=2
Solve for x
3(5x-4)=8x+2
Distribute
15x-12=8x+2
Move the variables to one side
15x-8x=2+12
7x=14
x=2
3 ( 5x - 4 ) = 8x + 2
First distribute the equation
By distributing the equation , your equation should look like
15x - 12 = 8x + 2 now subtract 8x on both sides in order to get the " x " alone
By subtracting, your equation should look like
7x - 12 = 2 Add 12 on both sides
By adding, your equation should look like
7x = 14 Divide both sides by 7
By dividing your equation should look like
x =2 which is your answer
3(5x-4)=8x+2
15x-12=8x+2
7x-12=2
7x=14
x=2
3(5x-4)=8x+2 distribute the 3
15x-12=8x+2 combine like terms
15x-8x=2+12
7x=14 now divide by 7
x=2
3(5x-4)=8x+2
15x-12=8x+2
7x=14
x=2
to prove 3(5x-4)=8x+2
first we have to find the value of x
multiply 3 with 5x and -4
we get 15x-12
15x-12=8x+2
by L.H.S. n R.H.S.
15x-12+12=8x+2+12
15x-8x=8x+14-8x
7x=14
7x/7=14/7
x=2
now,
put 2 in place of x
3{(5*2)-4}=(8*2)+2
3{10-4}=16+2
3*6=18
18=18
hence proved
Student Answers